QARAQALPAQ TILINDEGI RÁWISH FRAZEOLOGIZMLERDIŃ MÁNILIK ÓZGESHELIKLERI - Allaniyazov, А. (SCIENCE and SOCIETY, 2020)
Phraseologisms belonging to the group of adverbs in the Karakalpak language are among the questions requiring deep scientific research in linguistics. The article examines the specificity of the content of the adverb in phraseological combinations in the Karakalpak language. Typological analysis of phrases and expressions is also provided.